HLA-B54 is an independent risk factor for pneumonia in Japanese patients with interstitial lung disease: A multicenter retrospective cohort study. (November 2021) - Sakamoto, Noriho; Ishimoto, Hiroshi; Tahara, Masahiro; Kido, Takashi; Hara, Atsuko; Miyamura, Takuto; Okuno, Daisuke; Tokito, Takatomo; Yoshioka, Sumako; Morimoto, Shimpei; Takazono, Takahiro; Yamamoto, Kazuko; et al.
Abstract: Purpose: Pneumonia is a major cause of respiratory-related hospitalization and an important prognostic factor in patients with chronic interstitial lung disease (ILD). However, the relationship between the incidence of pneumonia and human leukocyte antigen (HLA) serotype has not been fully elucidated. Therefore, this study aimed to determine if there is a relationship between HLA serotype and the incidence of pneumonia in Japanese patients with ILD. Methods: The medical records of patients with ILD treated at any of three centers in Japan were reviewed to determine their HLA-A and HLA-B serotypes. The characteristics of patients with and without pneumonia were compared. Cox regression analysis was performed to identify risk factors for pneumonia and death in these patients. Results: One hundred and forty-four patients with ILD (pneumonia group, n = 27; non-pneumonia group, n = 117) and complete HLA serology data available were included. HLA-B54 positivity was significantly more common in the pneumonia group than in the non-pneumonia group (37.0% vs. 15.4%, p = 0.010). HLA-B54 positivity was also a significant risk factor for pneumonia (hazard ratio [HR] 4.166, 95% confidence interval [CI] 1.862–9.320, p = 0.001) and death (HR 4.050, 95% CI 1.581–10.374, p = 0.004) in patients with ILD. Furthermore, HLA-B54 positivity was a significant risk factor for pneumonia (HR 3.964, 95% CI 1.392–11.090, p = 0.010) and death (HR 8.131, 95% CI 1.763–37.494, p = 0.007) in patients with idiopathic pulmonary fibrosis. Conclusion: HLA-B54 positivity was a significant risk factor for pneumonia and death in patients with ILD, including those with idiopathic pulmonary fibrosis. Highlights: Pneumonia is a major cause of respiratory-related hospitalization in ILD patients. There is no report showing a relationship between HLA serotype and pneumonia. The present study demonstrated its relationship in Japanese patients with ILD.